Acute presentation of post-traumatic stress by COVID-19 - Reyes-Tejada, Alejandra L. (2022)
Introduction: COVID-19 has generated diverse reactions and social changes in different populations, which may influence mental health. Objective: To describe the characteristics and risk factors of post-traumatic stress by COVID-19 in the Peruvian population. Methods: A retrospective cohort was studied in 2276 people over 18 years of age. The diagnosis of post-traumatic stress disorder was obtained with the Short Post-traumatic Stress Disorder Rating Interview (SPRINT-E) scale (α = 0.92), which was crossed with important variables; association statistics were obtained. Results: The main risk factors for post-traumatic stress were being a woman (p < 0.001); having obesity or cardiovascular disease (p < 0.001); spending more hours per day being informed about the subject (p< 0.001); having a family member who had suffered from post-traumatic stress disorder (p < 0.001); having a relative who has suffered from COVID-19 (p = 0.045), having a relative or friend who has died from this disease (p = 0.020); having relatives with psychiatric diagnoses (p = 0.018); having a harmful habit (p < 0.001), suffering from depression, anxiety or stress (p < 0.001; for each of the three disorders). On the contrary, the older the age (p<0.001) and the higher the academic degree (p<0.001), the lower the risk of post-traumatic stress. Conclusion: The factors associated with post-traumatic stress due to COVID-19 in the Peruvian population are obesity or cardiovascular disease, possession of harmful habits, family psychiatric history, having family members infected or killed by COVID-19, and suffering from depression, anxiety or stress.